Polyhedral MnO nanocrystals anchored on reduced graphene oxide as an anode material with superior lithium storage capability. Issue 9 (November 2015) - Xu, Guobao; Jiang, Feng; Ren, Zhi-ang; Yang, Li-wen
Abstract: A novel composite of polyhedral MnO ( p -MnO) nanocrystals and reduced graphene oxide (RGO) nanosheets as a high performance electrode material for lithium ion batteries (LIBs) is prepared by homogeneous precipitation, subsequent reduction with hydrazine under microwave irradiation and final annealing procedure. The characterizations of structure and morphology reveal that p -MnO nanocrystals are homogeneously anchored onto the RGO nanosheets. The synergistic effect of the p -MnO nanocrystals with high crystallinity and RGO nanosheets makes the as-prepared nanocomposite possesses high contact area between electrolyte and electrode, uniform delivery of electrons and ions, short Li + insertion/extraction pathways, superior protection against volume change of electroactive materials and excellent electrical conductivity of the overall electrode during electrochemical processes. As an anode material for LIBs, the p -MnO/RGO nanocomposite exhibits superior electrochemical performances including large reversible capacity, excellent cyclic performance and high rate capability. For example, the p -MnO/RGO electrode shows a reversible capacity of 988.6 mA h g −1 after 120 cycles at a current density of 100 mA g −1 and delivers 591.1 mA h g −1 at a rate of 1600 mA g −1 . Our results highlight the importance of anchoring nanocrystals with special morphology on RGO nanosheets for maximum utilization of electroactive materials to enhance energy storage in high-performance LIBs.